Facts and Figures and Mental Illness and Other Personality Disturbances - The National Association for Mental Health:::::: (1952)
This document is a booklet of information which presents the public the facts about mental health and mental illness in the U.S. These booklet will be useful, for example, to mental health associations; to other organizations working on mental health programs; to writers, editors, commentators, and speakers; and other interested individuals. It is not intended to give here comprehensive report on all the facts, nor to provide refined figures or bibliographies for use in statistical studies.